Modus Korupsi Perbankan: Penyelewengan Klaim Asuransi Debitur Meninggal Dunia - Alfan Nur Zuhaid, Muhammad; Sasmita, Navy; Panji Perdana, Radite (UI Scholars Hub, 2025)
Lending by banks is generally covered by insurance as mitigation in the event of the borrower's death. The insurance can be in the form of insurance issued by general insurance companies or life insurance companies that have the aim of protecting not only the bank as a creditor but also the borrower's heirs so that the borrower's heirs do not need to be burdened to repay the remaining loans and on the other hand the bank's liquidity and profitability are maintained. At an ideal level, if the borrower dies, the bank will make an insurance claim to the insurance company, then the insurance company will check the completeness of the file and transfer some funds to the bank as stipulated on the insurance agreement. This research will focus on the corruption case of misappropriation of credit insurance claims on the death of borrower that occurred at Bank Jateng Kaligawe Sub-Branch Office, Semarang.